Religious tourism representations in the Algerian TV programs - kaci Dhehbiya, Ait (International Journal of Psychosocial Rehabilitation, 2022)
This study tackles religious tourism or spiritual tourism in Algeria. The Algerian government must find solutions to developing the national economy after the world crisis by investing in the tourism sector because it is an eternal source of people's income.The study also seeks to explore the roles of media, particularly television, in promoting the tourism industry in Algeria. Television has become a mediator between tourism and society.This descriptive analytical study of public and private TV channel programs enables us to understand their conception of the concept of religious tourism and how they present and value the spiritual tourism heritage.The principal questions posed in this study are: How do Algerian private and public TV channels present religious tourism?